2016
DOI: 10.1002/fld.4293
|View full text |Cite
|
Sign up to set email alerts
|

A modified Galerkin/finite element method for the numerical solution of the Serre‐Green‐Naghdi system

Abstract: Abstract. A new modified Galerkin / Finite Element Method is proposed for the numerical solution of the fully nonlinear shallow water wave equations. The new numerical method allows the use of low-order Lagrange finite element spaces, despite the fact that the system contains third order spatial partial derivatives for the depth averaged velocity of the fluid. After studying the efficacy and the conservation properties of the new numerical method, we proceed with the validation of the new numerical model and b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 61 publications
(157 reference statements)
7
47
0
Order By: Relevance
“…x " uL h tuu`"ǫh 3 uux ‰ x " mG h tmu`'boundary terms', so the kinetic energy part of the Hamiltonian density (2.23) can be replaced by 1 2 mG h tmu. for the temporal discretisation, as described and analysed in [22] for a flat bottom and in [23] for varying bottoms. This method can perform really well for smooth solutions due to its conservative properties.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…x " uL h tuu`"ǫh 3 uux ‰ x " mG h tmu`'boundary terms', so the kinetic energy part of the Hamiltonian density (2.23) can be replaced by 1 2 mG h tmu. for the temporal discretisation, as described and analysed in [22] for a flat bottom and in [23] for varying bottoms. This method can perform really well for smooth solutions due to its conservative properties.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Section 5.2 of [77]. Recently, [71] demonstrated that the fully nonlinear Serre-Green-Nagdhi (SGN) equations simulate this experiment with higher accuracy than weakly nonlinear models. As will be demonstrated below, our method, being fully nonlinear, captures nicely this phenomenon, as expected.…”
Section: Reflection Of Shoaling Solitary Waves On a Vertical Wall At mentioning
confidence: 90%
“…The extension of the region of validity of these models and their numerical implementation has been the subject of a great deal of work. Restricting attention to models that take into account an uneven seabed, we mention, for instance, i) the Boussinesq-type models [1], [2], [3], [4], [5], [6], [7], [8], [9], ii) the two layer models [10], [11], and iii) the Green-Nagdhi equations [12], [13], [14]. More details and references can be found in Chapter 7 of [15] and in the review articles [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…It would be instructive to calculate the rate of convergence of the iteration (5.24). Table 1 lists values for the rates of convergence [8] …”
Section: Remarkmentioning
confidence: 99%